Interaction of Selected Terpenoids From Dalbergia sissoo With Catalytic Domain of Matrix Metalloproteinase-1: An In Silico Assessment of Their Anti-wrinkling Potential. Issue 13 (December 2019) - Yasmeen, Shagufta; Gupta, Promila
Matrix metalloproteinase-1 (MMP-1) is a predominant collagenase enzyme that cleaves collagen fibers, contributing to skin wrinkling. Matrix metalloproteinase-1 inhibitors of herbal origin may provide an earnest probability to offer a novel curative approach against MMP-1-mediated collagenolysis, prompted by ultraviolet (UV)-induced overexpression of MMP-1. In this in silico study, we have explored the MMP-1 inhibitory potential of selected terpenoids from Dalbergia sissoo extracts. Two triterpenoids (lupeol and betulin), 1 diterpenoid (phytol), and 1 ester derivative of lupeol (lupeol acetate) were studied along with a reference inhibitor (doxycycline) using molecular docking approach. Non covalent interaction between the target ligands was found. Lupeol was found interacting with amino acid (AA) residues in the catalytic domain of MMP-1 with 3 hydrogen bonds (H-bond) formation, phytol with 1 and doxycycline with 2 H-bonds, whereas betulin and lupeol acetate were not able to form any H-bond with the AA residues in the catalytic site of the target protein. However, hydrophobic interaction between these ligands and protein was evident with select residues. The binding affinity of lupeol was highest (binding free energy, Δ G  = −8.24 kcal/mol), which was greater than reference drug, doxycycline (Δ G  = −8.05 kcal/mol). Lupeol acetate and phytol displayed a Δ G value of −7.12 and −7.06 kcal/mol, respectively, whereas betulin holds less binding affinity for the target receptor (Δ G  = −4.66 kcal/mol). In silico pharmacokinetic studies demonstrated drug-like properties of the ligand compounds. This study shows that hydroxyl groups present in the ligands play a substantial role in establishing protein ligand interaction via hydrogen bonding.